Differentiated Antiretroviral Therapy Distribution Models: Enablers and Barriers to Universal HIV Treatment in South Africa, Uganda, and Zimbabwe. (September 2019) - Duffy, Malia; Sharer, Melissa; Davis, Nicole; Eagan, Sabrina; Haruzivishe, Clara; Katana, Milly; Makina, Ndinda; Amanyeiwe, Ugochukwu
Abstract : Abstract: Emerging HIV treatment distribution models across sub-Saharan Africa seek to overcome barriers to attaining antiretroviral therapy and to strengthen adherence in people living with HIV. We describe enablers, barriers, and benefits of differentiated treatment distribution models in South Africa, Uganda, and Zimbabwe. Data collection included semistructured interviews and focus group discussions with 163 stakeholders from policy, program, and patient levels. Four types of facility-based and 3 types of community-based models were identified. Enablers included policy, leadership, and guidance; functional information systems; strong care linkages; steady drug supply; patient education; and peer support. Barriers included insufficient drug supply, stigma, discrimination, and poor care linkages. Benefits included perceived improved adherence, peer support, reduced stigma and discrimination, increased time for providers to spend with complex patients, and travel and cost savings for patients. Differentiated treatment distribution models can enhance treatment access for patients who are clinically stable.